Phylogenetic and Transmission Patterns of Extended-Spectrum β- Lactamase –Producing Escherichia Coli among Neonatal's Gut Flora in Indonesia - Sulistya, Rakhmatul Binti; Kuntaman, Kuntaman; Koendhori, Eko Budi; Happy, Terza Aflika; Setyarini, Wahyu (Folia Medica Indonesiana, 2021)
This study aimed to explore the phylogenetic pattern of Extended-spectrum β-lactamase-producing Escherichia coli in the gut flora of neonatal into groups A, B1, B2, D and tracing the presence of spreading among the age group of neonatal. Multiplex PCR was conducted to classify the phylogenetic group of ESBL producing E. coli into groups of commensals (A, B1) and pathogen (B2, D). The spread of bacterial agents among the host (neonatal) was conducted by the RAPD-PCR method with two random primers. Among 34 bacterial isolates were identified among early neonatal group A (22,2%), B1 (11,1%), B2 (22,2%) D (33,3%) and postneonatal groups A (8%), B1 (4%), B2 (36%) D (40%). It was not a statistically significant difference (p=0.388). The dominance of pathogenic groups B2 and D as many as 70,6%. From 34 samples was found 34 types of RAPD indicated there were not any bacterial spread among neonatal. The ESBL producing E. coli among early neonatal and postneonatal were dominated by the pathogenic group of B2 and D (total=70,6%), but they were not statistically significant. There was not any spreading of bacterial agents among individual gut flora of neonatal.